Estrategias de aprendizaje y su incidencia en el área de electricidad básica a estudiantes de la Unidad Educativa, Clemente Baquerizo, cantón Babahoyo, provincia los Ríos. - Santamaria Muñoz, Monica Alexandra (2017)
The main objective of this research work is to establish the relationship between learning strategies in the area of basic electricity, research that seeks to respond to the concerns of students and teachers by knowing new opportunities for development in the professional activity, knowing how learning strategies are taught in the classroom and how to improve this teaching, to ensure that students improve their learning and are able to regulate their own process and have the possibility of being autonomous in their learning. I have not found any work that addresses the use and teaching of strategies, by the teachers of the institution, so this research aims, first, to know the reality of teaching learning strategies in educational units, which facilitate their inclusion in the ordinary curriculum. It is, therefore, a descriptive investigation that can serve as a starting point for future research in this area. Second, with the results obtained and once analyzed the needs of teachers, propose changes in teacher training, and strengthen the knowledge of students through the application of learning strategies, expand their intelligence.